Thermo-desorption: a valid tool for mercury speciation in soils and sediments? - Reis, Ana Teresa
Mercury (Hg) speciation by thermo-desorption is considered an alternative to laborious sequential chemical procedures; hence its popularity has increased in the last years. In thiswork, steps were taken to improve the information obtained by Hg speciation through thermo-desorption, specifically to improve peak resolution and increase the number of species that can be identified. The thermo-desorption behavior ofHg bound to iron oxides was characterized, as well as a new Hg–humic acid synthetic standard material. In contrast to previous studies, the peak corresponding to the Hg fraction associated with humic acids was clearly separated from the mineral fraction, and identified in some natural samples. With increasing temperature, Hg species are released in the following order: HgCl2 = Hg associated with Fe2O3 b Hg associated with humic acids b HgS b HgO, with an overlap of HgCl2 and Hg associated with iron oxides. An evaluation of the effects of sample pre-treatment and storage on Hg speciation was also performed. It was found that sieving to b2 mm improved the sample homogeneity. The importance of fast sample analysis was highlighted, given that after 10 days of storage at room temperature, volatile Hg0 could no longer be identified in the sample. The suitability of thermo-desorption for mercury speciation in soils and sediments is discussed.